Analysis of Urban Expansion Process Based on GIS and RS in Suihua - Shuhua Zhang; Lijun Zhou; Xueping Zhang (2010 2nd International Conference on Information Engineering and Computer Science, 2010)
The earth observation technology of remote sensing can offer rich variable data of urban expansion and becomes the main approach to monitor urban expansion. To obtain the characteristics of urban expansion process of Suihua city, we extracted urban land information base in five periods remote sensing images (1976, 1990, 2001, 2006 and 2009) using GIS technology, with the help of expansion intensity model, spatial center of gravity transfer model, compact index, urban land fractal index and urban expansion elasticity coefficient we analyzed the area, direction and form feature of urban land expansion in Suihua city. The result shows that during the 33 years from 1976 to 2009, the urban land area of Suihua was continuously increased, in which the urban expansion scale and speed are the largest from 2001 to 2009, the urban expansion direction is mainly in the west and the south, the urban compactness index is reduced, and the form feature is complex.